Slandering Prophet Moses by Bani Isra’il - Osmani, Noor Mohammad; Rahman, Md. Habibur (2020)
Bani Isra’il, the followers of the Prophet Moses (Peace be upon him), did not maintain proper etiquette and manners with the Prophet Moses, who is regarded to be the greatest benefactor to Bani Isra’il. He delivered them from the slavery of Pharaoh and Egyptians. Allah swt granted him with amazing miracles by which Pharaoh and his army were defeated and faced divine punishment in the Sea, and Bani Isra’il were delivered to a Free land. In the ayah of Surah Al-Ahzab: 69, Allah swt has commanded the believers not to behave like Bani Isra’il, who slandered Moses with intolerable accusations, from which Allah swt cleared him.